Proceedings of the International Conference on Applied Cybersecurity (ACS) 2023 - Zantout, Hind; Ragab Hassen, Hani (Lecture Notes in Networks and Systems, 2023)
VIII, 67 p. 16 illus., 8 illus. in color.